Characterization and growth of lead telluride quantum dots doped novel fluorogermanate glass matrix. (February 2015) - El-Rabaie, S.; Taha, T.A.; Higazy, A.A.
Abstract: The present study investigates the growth of PbTe quantum dots embedded in a novel fluorogermante glass matrix. Optical absorption shows a large blue-shift which implies that the prepared PbTe quantum dots reflect strong quantum confinement effect. The nanoparticle sizes calculated from optical absorption spectra are found to be 3.2, 3.6, 6.1 and 7.3 nm for the glass samples heat-treated at 500 °C for 30, 60, 120 and 180 min, respectively. The optical band gap E opt values showed a decrease from 2.52 to 1.95 eV with the nanoparticle size increase. XRD analysis confirmed the formation of PbTe nanocrystals which exhibit cubic structure. The quantum dot size obtained from XRD pattern and TEM micrograph is very close to that calculated from optical absorption spectra.